Unit-Specific Rates of Hand Hygiene Opportunities in an Acute-Care Hospital. (28th December 2016) - Han, Angela; Conway, Laurie J.; Moore, Christine; McCreight, Liz; Ragan, Kelsey; So, Jannice; Borgundvaag, Emily; Larocque, Mike; Coleman, Brenda L.; McGeer, Allison
Abstract : OBJECTIVE: To explore the frequency of hand hygiene opportunities (HHOs) in multiple units of an acute-care hospital. DESIGN: Prospective observational study. SETTING: The adult intensive care unit (ICU), medical and surgical step-down units, medical and surgical units, and the postpartum mother–baby unit (MBU) of an academic acute-care hospital during May–August 2013, May–July 2014, and June–August 2015. PARTICIPANTS: Healthcare workers (HCWs). METHODS: HHOs were recorded using direct observation in 1-hour intervals following Public Health Ontario guidelines. The frequency and distribution of HHOs per patient hour were determined for each unit according to time of day, indication, and profession. RESULTS: In total, 3, 422 HHOs were identified during 586 hours of observation. The mean numbers of HHOs per patient hour in the ICU were similar to those in the medical and surgical step-down units during the day and night, which were higher than the rates observed in medical and surgical units and the MBU. The rate of HHOs during the night significantly decreased compared with day ( P <.0001). HHOs before an aseptic procedure comprised 13% of HHOs in the ICU compared with 4%–9% in other units. Nurses contributed >92% of HHOs on medical and surgical units, compared to 67% of HHOs on the MBU. CONCLUSIONS: Assessment of hand hygiene compliance using product utilization data requires knowledge of the appropriate opportunities for hand hygiene. We have provided a detailed characterization of these estimates across a wide range of inpatient settings as well as an examination of temporal variations in HHOs. Infect Control Hosp Epidemiol 2017;38:411–416